Tetra(3,4-pyrido)porphyrazines Caught in the Cationic Cage: Toward Nanomolar Active Photosensitizers - Machacek, Miloslav; Demuth, Jiri; Cermak, Pavel; Vavreckova, Magda; Hruba, Lenka; Jedlickova, Adela; Kubat, Pavel; Simunek, Tomas; Novakova, Veronika; Zimcik, Petr (Journal of medicinal chemistry, 2016)
Investigation of a series of tetra(3,4-pyrido)porphyrazines (TPyPzs) substituted with hydrophilic substituents revealed important structure-activity relationships for their use in photodynamic therapy (PDT). Among them, a cationic TPyPz derivative with total of 12 cationic charges above, below and in the plane of the core featured a unique spatial arrangement that caught the hydrophobic core in a cage, thereby protecting it fully from aggregation in water. This derivative exhibited exceptionally effective photodynamic activity on a number of tumor cell lines (HeLa, SK-MEL-28, A549, MCF-7) with effective concentrations (EC50) typically below 5 nM, at least an order of magnitude better than the EC50 values obtained for the clinically approved photosensitizers verteporfin, temoporfin, protoporphyrin IX, and trisulfonated hydroxyaluminum phthalocyanine. Its very low dark toxicity (TC50 > 400 μM) and high ability to induce photodamage to endothelial cells (EA.hy926) without preincubation suggest the high potential of this cationic TPyPz derivative in vascular-targeted PDT.
Keywords: Cell Survival; Dose-Response Relationship, Drug; Photochemotherapy; zvířata; Photosensitizing Agents; Structure-Activity Relationship; buňky 3T3; fotosenzibilizující látky; Pyridines; Molecular Structure; metaloporfyriny; HeLa buňky; Tumor Cells, Cultured; 3T3 Cells; Mice; Cations; molekulární struktura; viabilita buněk; Animals; endoteliální buňky; Endothelial Cells; vztahy mezi strukturou a aktivitou; fotochemoterapie; kationty; nádorové buňky kultivované; MFC-7 buňky; pyridiny; Metalloporphyrins; lidé; Humans; HeLa Cells; myši; MCF-7 Cells; vztah mezi dávkou a účinkem léčiva